Cenozoic Subsidence Features of Beitang Sag and Relationship with Tectonic Evolution - 张婷婷 王华 岳勇 黄传炎 张立伟 (Journal of earth science (Wuhan, China), 2009)
Based on the application of the EBM basin modeling software and 2-D seismic profiles, the Paleogene and Neogene subsidence histories of the Beitang （北塘） sag are simulated with the back-stripping technique, and the relationship between subsidence character and tectonic revolution is discussed. Moreover, the result of the basin modeling reveals that the subsidence history of the Beitang sag has the characteristics of several geological periods, and these succeeding periods have shown certain inheritance and difference characteristics. At the early （Es3） and middle （Es2-Es1） rifting periods, the subsidence reaction of the Beitang sag was mainly in the charge of tectonic activity, while at the late （Ng-Nm＋Q） rifting period-post rifting period and post rifting subsidence-acceleration period-the subsidence type is mainly that of thermal subsidence or regional depression effect; from the beginning of the subsidence history to the end, the reason for the basin subsidence has changed from tectonic activity to non-tectonic activity.